The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.21273/horttech.5.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Eating Quality and Other Characteristics of New Mexico Pecan Cultivars Harvested over Three Years

Abstract: This work is the result of 3 years of collaborative research between Mississippi State Univ. and New Mexico State Univ. Physical, chemical, and sensory characteristics were studied to assess eating quality of popular New Mexico pecan (Carya illinoinensis) cultivars. The force and energy necessary to break (shear) pecan nuts, and Hunter `a' and hue angle values varied with harvest year and cultivar. All other traits, including sensory evaluation results, varied only with culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…All nuts including pecan are good protein sources, containing few saturated fats, cholesterol free and high in unsaturated fats (Silva et al, 1995). The unsaturated fats in pecan are protected against oxidation by the high concentration of y-tocophenol and polymeric flavones (Haddad et al, 2006 andAttia &Wafaa, 2007).…”
Section: Intoductionmentioning
confidence: 99%
“…All nuts including pecan are good protein sources, containing few saturated fats, cholesterol free and high in unsaturated fats (Silva et al, 1995). The unsaturated fats in pecan are protected against oxidation by the high concentration of y-tocophenol and polymeric flavones (Haddad et al, 2006 andAttia &Wafaa, 2007).…”
Section: Intoductionmentioning
confidence: 99%
“…Sensory research has demonstrated that the flavor of pecans can indeed depend on the pecan genetics. Two studies (Magnuson et al, 2016;Silva et al, 1995) showed that different clones have different flavor profiles, but the authors also remarked that environmental conditions probably played a larger role than genetics. The studies did not include native pecans and used a trained sensory panel of 6 to 12 individuals.…”
mentioning
confidence: 99%